Single centre randomized comparative trial of lateral internal sphincterotomy versus 2% diltiazem in chronic anal fissure - Sritharan, Hariharan; Ashok Kumar, Naren Kumar; Syed Ibrahim M. S., Mohamed Ismail (International Surgery Journal, 2020)
Background: Anal fissures are often encountered in surgical practice with surgery the gold standard management for chronic anal fissures. Recently the widespread use of pharmacologic agents for chronic fissures has increased. In our study we compare topical 2% diltiazem with lateral sphincterotomy with respect to symptoms such as relief of pain, ulcer healing, and side effects of treatments. Methods: A prospective comparative study, a total of 80 patients were randomized into 2 groups 40 each. Group A patients were subjected to open internal lateral sphincterotomy and group B to 2% topical diltiazem. The patients in both groups were followed up at 1st, 4th, 14th weeks and 6 months in OPD and were assessed for pain, sphincter tone and complications. Results: In group A (lateral anal sphincterotomy), patients achieved a good pain relief with a mean pain score of 1.98 by one week post procedure whereas group B (2% diltiazem) had taken 14 weeks to achieve similar pain relief (pain score of 1.5). At the end of 6 months, healing of fissure was noted in 100% of group A and in 90% of group B. 4 patients (10%) had recurrences in group B. Flatus incontinence was reported in 2 patients (5%) in group A although transient. Conclusions: Lateral anal sphincterotomy is superior to 2% diltiazem especially in healing of fissure, pain relief, quality of life and recurrence. Pharmacologic agents should be reserved for patients who are unfit or unwilling for surgery or can be used as a bridge therapy till sphincterotomy can be planned.